2011
DOI: 10.1152/ajpheart.00886.2010
|View full text |Cite
|
Sign up to set email alerts
|

Liver growth factor treatment restores cell-extracellular matrix balance in resistance arteries and improves left ventricular hypertrophy in SHR

Abstract: Conde MV, Gonzalez MC, Quintana-Villamandos B, Abderrahim F, Briones AM, Condezo-Hoyos L, Regadera J, Susin C, de Diego JJ, Delgado-Baeza E, Diaz-Gil JJ, Arribas SM. Liver growth factor treatment restores cell-extracellular matrix balance in resistance arteries and improves left ventricular hypertrophy in SHR. Am J Physiol Heart Circ Physiol 301: H1153-H1165, 2011. First published June 3, 2011 doi:10.1152/ajpheart.00886.2010.-Liver growth factor (LGF) is an endogenous albumin-bilirubin complex with antihypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 66 publications
2
30
0
1
Order By: Relevance
“…Hypertension is associated with cardiovascular fibrosis, remodeling and endothelial dysfunction, alterations where oxidative stress plays a key role [37][38][39]. Similar cardiovascular alterations have been found in adult IUGR rats [40][41][42] and therefore oxidative stress has been proposed as a possible mechanism implicated in fetal programming of hypertension [7,43].…”
Section: Discussionmentioning
confidence: 69%
“…Hypertension is associated with cardiovascular fibrosis, remodeling and endothelial dysfunction, alterations where oxidative stress plays a key role [37][38][39]. Similar cardiovascular alterations have been found in adult IUGR rats [40][41][42] and therefore oxidative stress has been proposed as a possible mechanism implicated in fetal programming of hypertension [7,43].…”
Section: Discussionmentioning
confidence: 69%
“…We have previously published that 12-day LGF treatment of SHR reduces blood pressure and LVH, markedly improving vascular fibrosis and vasodilatation [28,29]. Since all these alterations in the SHR model are linked to oxidative stress [44,45], we hypothesize that LGF might be able to exert its regenerative actions, at least in part, through an antioxidant mechanism.…”
Section: Discussionmentioning
confidence: 95%
“…LGF is an endogenous factor which is not detected in physiological conditions but it increases its concentration in plasma in hepato-biliary disorders, both in humans and rats [26,27]. We have previously demonstrated that short treatment (12 days) with LGF of spontaneously hypertensive rats (SHRs) significantly reduces blood pressure, vascular fibrosis, endothelial dysfunction and left-ventricular hypertrophy [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Fibrillar type I/III collagens are the most abundant in vascular walls 49 and they play an important contribution to the rigidity of the arterial wall of resistance arteries in hypertension 6,9,31,50 . In this study, MA from HFD show augmented content of type I collagen, which comprises 60% of the vascular wall collagens 51 , without changes in type III collagen.…”
Section: Discussionmentioning
confidence: 99%